MISSIONARIES AND WOMEN EMANCIPATION IN IGBOLAND - Anyanwu, Herbert Onyema (Journal of Dharma, 2001)
The biblical concept of the origin of the woman that she was created from the ribs Of a man presupposes woman to be inferior to men. In the traditional Igbo Society, though the concept of women being made from the rib of man is absent, women were still placed under men. Women have remained in some measure passive members of the human world. They were banished to the back of the house where they did the main house chores, cared for the young ones and prepared and catered food in the house. It is therefore, the wish of this paper to highlight the limited role of women in the traditional society and to show a progressive assumption of greater role through the instrumentality of the missionaries.